Concurrent sintilimab with sequential chemoradiotherapy for unresectable, stage III non-small cell lung cancer: a retrospective study - Tang, Shi; Cong, Xiaofeng; Zheng, Dan; Chen, Chen; Liu, Zengguang; Gao, Jie; Zhang, Huimin; Zhang, Youhao; Liu, Ziling (Frontiers in Oncology, 2023)
Background: Concurrent programmed death 1 (PD-1) or programmed death ligand 1 (PD-L1) inhibitors with sequential chemoradiotherapy (SCRT) have been reported in only a limited number of studies involving patients with unresectable stage Ⅲ non-small-cell lung cancer (NSCLC). A retrospective study was conducted to systematically analyze the efficacy and safety of the emerging therapy among Chinese patients. Materials and Methods: We included patients with unresectable, stage III NSCLC who received concurrent sintilimab with chemotherapy or chemotherapy alone for 3-6 cycles, followed by radical radiotherapy at the First Hospital of Jilin University from Dec 15, 2019, to Jul 15, 2022. The primary end point was the objective response rate (ORR). The secondary end points included progression-free survival (PFS), overall survival (OS), 12-month and 18-month PFS rates, the duration of response (DoR), and safety. Results: The retrospective study involved 77 patients, of which 49 receiving concurrent sintilimab with SCRT were assigned to cohort A, and 28 receiving SCRT alone were assigned to cohort B. The ORR was significantly higher in cohort A (79.6%, 95% CI 65.7–89.8) than in cohort B (35.7%, 95% CI 18.6–55.9) (p<0.001). Median PFS was significantly longer in cohort A than in cohort B (NR [95% CI 21.4–NR] vs. 16.0 months [13.0–22.5]; HR 0.375, 95% CI 0.192–0.735; p=0.003). The PFS rates at 12 and 18 months were 84.8% (95% CI 75.0–95.9) and 71.3% (95% CI 58.7–86.7) in cohort A and 75.0% (95% CI 60.6–92.9) and 38.3% (95% CI 23.7–61.7) in cohort B, respectively. Grade 3 or 4 adverse events (AEs) were reported in 19 patients (38.8%) and seven patients (25.0%) in two cohorts, respectively. Grade 3 or 4 pneumonitis or immune-mediated pneumonitis, radiation pneumonitis, and pneumonia occurred in five (10.2%), four (8.2%), and two (4.1%) cohort A patients, and zero, two (7.1%), and two (7.1%) cohort B patients, respectively. Only cohort A reported AE leading to death in one (2.0%) patient (immune-mediated pneumonitis). Conclusion: Concurrent sintilimab with SCRT resulted in a significantly better ORR and longer PFS than SCRT alone, with manageable safety profiles in Chinese patients with unresectable stage III NSCLC.